Comparing Chest Radiograph Lesion Areas in Pulmonary Tuberculosis Patients with and without Diabetes Mellitus: A 2023 Study at Waled Hospital, Cirebon, Indonesia - Fatihah, Hapsari Bunga; Latief, Muhammad Amar; Herdwiyanti, Menik (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: The Global Tuberculosis Report emphasizes a significant number of TB cases, and Indonesia is the second country in Southeast Asia with the most TB cases. Prevalence of TB increases along with the increase of Diabetes Mellitus (DM) prevalence, which both are known to have a negative impact on each other. Clinical symptoms in TB with DM differ from those in TB without DM. However, whether there is any difference in radiology examinations is unknown. This can be a consideration for determining patient therapy based on differences in the chest radiographs. Aims: To determine the Lesion Area Difference on Chest Radiographs of Pulmonary Tuberculosis Patients with and without Diabetes Mellitus at Waled Hospital in 2023. Methods: There were 96 data points based on the first taken chest radiograph from both inpatient and outpatient data, which were obtained from medical records in 2023 at Waled Hospital, Cirebon. Statistical analysis was performed using the Chi-Squared comparative test in this observational study with a cross-sectional design. Results: There were 69 tuberculosis (TB) patients without diabetes mellitus (DM) and 27 TB patients with DM. Overall, patients had minimal lesions (14.6%), moderate lesions (26.0%), and far-advanced lesions (59.4%). The Chi-Square analysis from these samples showed a p-value of 0.870. Conclusion: There is no difference in lesion area on chest x-rays in pulmonary tuberculosis patients with or without diabetes mellitus. Further research is expected to include the type of TB and history of treatment for either TB or DM.